Post - war condition of Britain - Cole, G.P.H. (London, 1956)
Any book that attempts to deal with current statisties is bound to A e out of dute in many respecte before it appears. Both official and unofficial stationes are published at various times throughout e and there is no one date at which all the statistics for a par feeler yer are available and none of them have been niperseded, or dered of only historical interest, by later figures. In finishing this I did my best to pick a time of year late October 1955 at which most of the figures for the previous year, 1954, were available, but I am wow correcting the paged proof sheets in June 1956, and already a good many though not nearly all, of the data for 1955 have come to hand It is quite out of the question, for reasons of cost, to insert these later figures in the text, as this would mean re-setting many of the tables, and accordingly the account of post-war Britain rendered in the main text ends, for the most part, with 1954, though I have inserted a number of references to conditions during the first half of 1955. In addition, I have provided an Appendix giving the more important figures that have become available since my book went to the printers. This of course means that, as far as the main text goes, the record is closed before the beginning of the credit squeeze' and the return to high interest rates which have considerably altered the economic situation in 1956; and there are quite a number of points at which I should need to express myself differently if I were writing now. Similarly, my chapter on Monopolies and Restrictive Practices was written before the Govern ment produced its Bill, now before Parliament, dealing with these matters; and the widespread discussion of "automation' and the 'redun dancy' crisis in the motor-car industry have flared up since my book was sent to the printers. Such time-lags are unavoidable, and I do not need to apologize for them. Nor is it my fault that books take nowadays a long time to produce, or that this particular book was unfortunate in being in the printers' hands at a time when production was being seri ously interfered with by a trade dispute. The reader who is particularly concerned with the most recent developments must be left to search out the latest figures for himself with the aid of the fairly full list of sources given in the bibliography.
Keywords: Economics